Metode Analisis Natrium Benzoat pada Makanan dan Minuman: Literatur Review - Erlangga Muhamad Prayuda; Febi Febriani Hasanah; Rika Valensia; Nurma Dwi Rahmawati; Marsah Rahmawati Utami (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Preservatives are food additives that can inhibit the growth of microorganisms so that food does not get stale easily. Sodium benzoate is one of the preservatives that is allowed to be used in food but within a predetermined limit of <1 g / kg according to BPOM RI. The purpose of this review is to find out an overview and provide information about the method of analyzing sodium benzoate levels in food and comparing the results with the provisions. The method used is literature review from various journals with a span of 10 years. The results of this study, the method of analyzing sodium benzoate in food can be carried out qualitatively and quantitatively. Qualitative tests can use the addition of FeCl3, test kits, and KLT, while quantitative tests can use KCKT, spectrophotometry UV-Vis and titration. The samples studied from 11 journals obtained were syrup, sauce (tomato and chili), soy sauce, beverage and strawberry jam products produced industrially and/or home-produced. The conclusion of the various methods tested is that there are still many food producers who use sodium benzoate as a preservative, but not all samples studied are in accordance with the provisions